2016
DOI: 10.1097/01.aoa.0000482623.48409.5b
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes Following an Earlier Postterm Labour Induction Policy: A Historical Cohort Study

Abstract: (BJOG. 2015;122:1377–1385) The aim of the study undertaken was to assess the changes in perinatal outcomes in children born from 37 weeks of gestation after implementation of a more proactive labor induction practice from 2009. This register-based historical cohort study included all newborns in Denmark delivered from January 1, 2000 to December 31, 2012. To reduce the random year-to-year variation, the 13-year study period was subdivided into 5 intervals of 3, 3, 3, 2, and 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A Danish national cohort study covering a twelve-year period found that, while induction rates had more than doubled in that time, the stillbirth rate had fallen by one per thousand newborns (Hedegaard et al, 2014). Notably however, the number of women smoking in pregnancy, which also increases the risk of stillbirth, had halved during this period and more high-risk women were being induced.…”
Section: Induction Of Labourmentioning
confidence: 99%
“…A Danish national cohort study covering a twelve-year period found that, while induction rates had more than doubled in that time, the stillbirth rate had fallen by one per thousand newborns (Hedegaard et al, 2014). Notably however, the number of women smoking in pregnancy, which also increases the risk of stillbirth, had halved during this period and more high-risk women were being induced.…”
Section: Induction Of Labourmentioning
confidence: 99%